Improving Governance of Indonesia's Peatlands and Other Lowland Ecosystems - World Bank (World Bank, Washington, DC, 2021)
The report aims to advance a policy dialogue on how to address sustainability challenges from lowland developments. The specific approach discussed in this report is the "landscape approach" which, in turn, calls for improved "landscape governance." As a technical background study, the report serves four functions. First, it summarizes the principles of a landscape approach, elaborated in the context of Indonesia's lowlands through two previous technical studies. Second, it takes stock of current governance challenges in Indonesia's lowlands, focusing on those related to the government sector, and discusses how these challenges currently prevent a landscape approach from being implemented in Indonesia's lowlands. Third, it reviews Indonesia's recent efforts to address the governance challenges in the management of peatlands and other lowland ecosystems. Fourth, it offers recommendations on options to improve lowland governance in order to shift toward integrated management of Indonesia's lowlands based on a landscape approach.The report focuses on the lowland areas in eight fire-prone provinces, and on key landscape governance issues related to peatlands. Indonesia suffered many years of repeated fires and haze crises, with landmark events in 1982/83, 1997/98, 2002, 2006, 2009, and 2015. The 2015 El Niño-driven fires were particularly extensive and costly. Almost 80 percent of the 2015–16 fires occurred within the lowland areas in eight fire-prone provinces—Central Kalimantan, East Kalimantan, Jambi, Papua, Riau, South Kalimantan, South Sumatra, and West Kalimantan—which together account for 87 percent of lowland areas nationally. The report highlights the importance of sustainable landscape management of lowland areas, particularly of the peatlands within lowland boundaries, for achieving the Government of Indonesia’s objective in preventing land and forest fires.